Long-term Results of Totally Laparoscopic Aortobifemoral Bypass. Issue 5 (November 2016) - Lecot, F.; Sabbe, T.; Houthoofd, S.; Daenens, K.; Fourneau, I.
Abstract : Objectives: The aim was to estimate the long-term results and patency rates of totally laparoscopic aortobifemoral bypass in aorto-iliac occlusive disease (AIOD). Methods: All 87 patients who received a laparoscopic aortobifemoral bypass for AIOD on an intention to treat basis between October 2003 and October 2013 were identified. All operations were performed by the same surgical team using a totally laparoscopic technique. Demographic, pre-operative, peri-operative, and follow up variables were collected and analyzed. Patients were followed up at 1 month post-operatively and annually thereafter. Patency rates were calculated in accordance with published patency reporting standards. Results: The median age was 57 years (range 40–78 years). The conversion rate was 20.6% overall. The thirty-day post-operative mortality was 1.1%. Six patients required early re-intervention. There were no graft infections. The median length hospital stay was 6 days (range 4–39 days). The mean follow up was 58.0 months (range 1–133 months). Graft limb based primary, primary assisted, and secondary patency rates were respectively 96.1%, 98.1% and 99.4% at 1 year, and 83.0%, 92.0% and 97.0% at 5 years. Conclusion: Totally laparoscopic aortobifemoral bypass is a safe alternative to open surgery in selected patients, with excellent long-term patency rates, albeit at the cost of a steep learning curve.